Pengaruh Persepsi dan Minat Mahasiswa terhadap Motivasi Berkarir sebagai Guru - Erni Harlina Isdiati Erni; Arif Wahyu Wirawan; Muhammad Nukha Murtadlo (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
This study aims to analyze the influence of students’ perceptions and interests on their motivation to pursue a teaching career through the Teacher Professional Education Program (PPG). A quantitative approach was employed using a survey method. The population of this study consisted of final-year students from the Economics Education Study Program at Universitas Negeri Semarang, with a total sample of 200 students selected through purposive sampling based on criteria of understanding PPG and expressing interest in becoming teachers. The research instrument was a closed-ended questionnaire using a five-point Likert scale, which was tested for validity and reliability. Construct validity was examined through exploratory factor analysis (EFA), while reliability was measured using Cronbach’s Alpha with a threshold of α ≥ 0.70. Data analysis was conducted in two stages: descriptive analysis and inferential analysis using multiple linear regression. The results indicate that both students’ perceptions and interests have a positive and significant effect on their motivation to participate in the PPG and pursue a teaching career. These findings provide practical implications for the development of promotional strategies and educational policies to strengthen teacher professionalism in higher education institutions.